Korovkin type theorem in the space $C_{b}[0,\infty)$: Dedicated to Professor Gheorghe Coman on the occasion of his 80th anniversary - FINTA, Zoltán (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
A Korovkin type theorem is established in the space $C_{b}[0,\infty)$ of all continuous and bounded functions on $[0,\infty)$ for a sequence of positive linear operators, the approximation error being estimated with the aid of the usual modulus of continuity. As applications we obtain quantitative results for $q$-Baskakov operators. Mathematics Subject Classification (2010): 41A36, 41A25.